A Survey Study To Assess The Status Of Bala And Morbidity Among The Individuals Of Jaipur City In Yamadamstra Kala - Pal, Surender; Sharma, Kamalesh Kumar; Agrawal, Sarvesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Various health care measures are mentioned in Ayurveda to maintain the health of the healthy persons, like Dincharya, Ritucharya, Ahara-Vihara, Adharniya-Dharniya Vega, Achar rasayan, Rasayana and Vajikarana. Ritucharya or seasonal regimen teaches us how to adapt various seasons and seasonal changes in terms of small adjustments which we need to make during various seasons with respect to diet, lifestyle and behaviour. Ritusandhi is the transition period between two seasons. Therefore, the status of Bala (Sharira Bala, Satva and Agni) should be assessed. Method: In this study the assessment of Bala (Sharira Bala, Satva and Agni) and morbidity of people during Yamadamstra Kala (6 to 21 November 2019) and one month before (5to 20 October 2019) has been done with the help of survey and the hospital’s OPD data respectively. Result: Insignificant change has been found in Bala (Sharira Bala, Satva and Agni) of 300 healthy individuals. Morbidity was increased in new OPD patients during Yamdanstra Kala. Conclusions: There was no effect of Yamadamstra Kala on Bala (Sharira Bala, Satva and Agni) according to survey of healthy volunteers but morbidity is increased during yamadamstra kala in comparison of one month before.